2015
DOI: 10.1093/mnras/stv2633
|View full text |Cite
|
Sign up to set email alerts
|

Inclination-induced polarization of scattered millimetre radiation from protoplanetary discs: the case of HL Tau

Abstract: Spatially resolved polarized millimeter/submillimeter emission has been observed in the disk of HL Tau and two other young stellar objects. It is usually interpreted as coming from magnetically aligned grains, but can also be produced by dust scattering, as demonstrated explicitly by Kataoka et al. for face-on disks. We extend their work by including the polarization induced by disk inclination with respect to the line of sight. Using a physically motivated, semi-analytic model, we show that the polarization f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
176
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(200 citation statements)
references
References 27 publications
(47 reference statements)
23
176
1
Order By: Relevance
“…This is the same argument that we used in Yang et al (2016a) of polarization degree with inclination angle in a geometrically and optically thin disk. The difference is that this trend continues all the way to i = 90…”
Section: Chapter 3)supporting
confidence: 55%
See 1 more Smart Citation
“…This is the same argument that we used in Yang et al (2016a) of polarization degree with inclination angle in a geometrically and optically thin disk. The difference is that this trend continues all the way to i = 90…”
Section: Chapter 3)supporting
confidence: 55%
“…Such a config-uration would produce a polarization pattern that appears inconsistent with the pattern observed in HL Tau (Stephens et al 2014). The apparent inconsistency led Yang et al (2016a) to propose that the disk polarization in HL Tau comes from dust scattering, based on Kataoka et al (2015) theory of scattering-induced millimeter polarization (see also Kataoka et al 2016a). Specifically, they show that dust scattering in a disk inclined to the line of sight can naturally explain why the observed polarization vectors are roughly parallel to the minor axis and the distribution of polarized intensity is elongated along the major axis.…”
Section: Introductionmentioning
confidence: 99%
“…The unpolarized light is scattered by other grains because of the high scattering opacity. Due to the ring-like structure of the emission and the inclination of the disk, the distribution of the incoming flux to the scattering dust grains has anisotropies (see also Yang et al 2016). As a result, the total flux has a residual polarization corresponding to the anisotropic radiation field.…”
Section: Resultsmentioning
confidence: 99%
“…Note that, during the preparation of the manuscript, Yang et al (2016) independently found that the interpretation of the millimeter-wave polarization of HL Tau due to dust scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Close to the peak, the observed lower polarization percentage at 0.88 mm, then 6.9 mm (Figure 6), may be because of the more significant polarization canceling effect at 0.88 mm. The high optical depth at 0.88 mm may further lead to additional (de-)polarization due to scattering (Kataoka et al 2015;Yang et al 2015).…”
Section: Discussionmentioning
confidence: 99%